Clinical and economic analysis of using dapagliflozin in patients with chronic kidney disease in the Russian Federation - Sergey V. Nedogoda; Alla S. Salasyuk; Irina N. Barykina; Viktoria O. Smirnova; Ekaterina A. Popova (ZAO "Consilium Medicum", 2021)
Aim. To evaluate the clinical and economic efficiency of the use of dapagliflozin in patients with chronic kidney disease (CKD) stages 24 in Russian Federation. Materials and methods. Cost-effectiveness (utility) analysis has been carried out. Mathematical model has been developed, adapted to the healthcare system of the Russian Federation by using Russian cost and patients characteristics inputs. Life years (LYG) and quality-adjusted life years (QALY) were used as efficiency criteria. Only direct medical costs were taken into account. Cost-effectiveness (utility) analysis was carried out in the short-term (3 years) and long-term horizons (10 years). Results. The use of dapagliflozin in addition to standard therapy (ST) versus ST for CKD stage 24 in the short term (3 years) is cost effective: it allows you to additionally receive 0.042LYGs/0.035QALYs, while the incremental cost of an additional year of life is 827,399 rubles, an additional year of life adjusted for quality is 988,424 rubles, which does not exceed the threshold of willingness to pay according to World Health Organization recommendations 2 191,061 rubles. In the long term (10 years), the use of dapagliflozin in addition to ST will provide an additional 0.437LYGs/0.356QALYs and lead to a decrease of direct medical costs by 96,546 rubles on average for 1 patient. Thus, in the horizon of 10 years, the dapagliflozin + ST regimen is strictly preferred or dominant at the same time more effective and less costly. Conclusion. The use of dapagliflozin in addition to ST for the treatment of patients with CKD stages 24 in the long-term horizon (10 years) allows to extend the stay in the pre-dialysis stages of CKD by 8 months an average of 1 patient. Dapagliflozin therapy regimen and ST in a cohort of 1,000 patients with CKD stages 24 on the horizon of 10 years will avoid 30 hospitalizations due to heart failure (namber needed to treat NNT 34), 59 cases of acute kidney injury (NNT 18), 73 deaths from all causes (NNT 14).